DISTRIBUSI SPASIAL DAN EPIDEMIOLOGI HIV-AIDS DI PROVINSI SUMATERA SELATAN TAHUN 2021 - Sylpi Kharisma Afrisae; najmah najmah; Irma Tiara Rizki; Muyono; Yusri (Jurnal Endurance, 2023)
HIV and AIDS is a global health problem and is a disease for which there is no medicine that can completely cure it. Based on a report from the South Sumatra Provincial Health Office, there were 329 new HIV cases and 121 AIDS cases recorded in 2021. This research aims to find out what causes HIV and AIDS in South Sumatra Province. This study used HIV and AIDS case data obtained from the South Sumatra Provincial Health Office from 2017 to 2021. This research is a descriptive study with an ecological study design. Based on the results obtained, HIV and AIDS cases during 2017-2021 have experienced ups and downs. In 2018 HIV and AIDS has increased, namely 435 HIV cases and 246 AIDS cases. In 2019 HIV and AIDS cases have decreased, namely 433 HIV cases and 233 AIDS cases. In 2021 HIV and AIDS cases have decreased again, namely 329 HIV cases and 121 AIDS cases. It can be concluded that the groups most at risk of contracting HIV and AIDS are productive age, male sex and living in Palembang city.